A systematic review on hydrogen production via hydrochar-based gasification - Sabah Mariyam (14150859) (2025)
Hydrogen (H2) yields from various gasification and hydrothermal processes demonstrate significant variability depending on feedstock, catalysts, and process parameters. This systematic review explores hydrogen production through hydrochar-based gasification technologies, focusing on the unique properties of hydrochar derived from biomass. Known for its ability to enhance syngas production, especially hydrogen, hydrochar's porous structure, high surface area, and active catalytic sites significantly improve syngas quality and hydrogen yield. Studies show that supercritical water gasification (SCWG) of almond shells with hydrochars yielded up to 11.63 mmol/g, while catalytic subcritical and SCWG of waste tires reached 19.7 mmol/g. Hydrothermal carbonization (HTC) coupled with gasification yields as high as 76.7 g H2/kg biochar for sewage sludge hydrochar, with processes like anaerobic digestion and HTC producing 1278 mL/g from hemp hurd hydrochar. Key aspects such as the catalytic influence of hydrochar, the role of additives and co-catalysts, and optimization of gasification parameters, including temperature, pressure, and equivalence ratios, are explored. The review also delves into hydrochar preparation advancements, such as alkali and alkaline earth metals (AAEMs) incorporation, and highlights hydrochar's role in reducing tar formation, enhancing H2/CO ratios, and stabilizing syngas heating value. Other Information Published in: International Journal of Hydrogen Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ijhydene.2025.150933